1) 10 chia hết cho 2x + 1\(\Rightarrow2x+1\in\text{Ư}\left(10\right)\)
Ư(10) = {1; 2; 5; 10}
* 2x + 1 = 1 => 2x = 0 => x = 0
* 2x + 1 = 2 => 2x = 1 => x = 1/2
* 2x + 1 = 5 => 2x = 4 => x = 2
* 2x + 1 = 10 => 2x = 9 => x = 9/2
Vậy x = {0; 1/2; 2; 9/2} thì 10 chia hết cho 2x + 1
#Học tốt!!!
~NTTH~
\(a )\) \(Ta \) \(có :\) \(3 \) \(⋮\)\(2x + 1\)
\(\Leftrightarrow\)\(2x + 1\) \(\in\)\(Ư\)\(( 3)\) \(= \) { \(1 ; 3 \) }
\(Ta lập bảng :\)
2x + 1 | 1 | 3 |
x | 0 | 1 |
Vậy : x \(\in\){ 0 ; 1 }
b ) Ta có : 2x - 4108 \(⋮\)2x + 3
\(\Leftrightarrow\)( 2x + 3 ) - 4111 \(⋮\)2x + 3
\(\Leftrightarrow\)2x + 3 \(\in\)Ư( 4111 ) = { 1 ; 4111 }
Ta lập bảng :
2x + 3 | 1 | 4111 |
x | - 1 ( loại ) | 2054 |
Vậy : x = 2054